OTHER MEASURES OF CRIMINAL-LEGAL NATURE: DEFINITION, LEGAL NATURE, SYSTEM - T. Nepomnyashchaya (Правоприменение, 2017)
УДК 343The article is devoted to the analysis of the concept of the legal nature and the system of other measures of criminallegal nature, specified in the Criminal legislation of the Russian Federation and the problems of application of these measures in the judicial practice. The author pays attention to the fact that these measures are quite common in the judicial practice, especially conditional sentence. The legislator establishes three of other measures of criminal-legal nature in section VI of the RF Criminal Code: compulsory measures of a medical nature, confiscation of property and judicial penalty. But the author of the article aims to prove that the system of other measures of criminal-legal nature is not exhausted by these three measures. The article substantiates the statement that the measures in question constitute independent institute of criminal law. The author analyzes in details the concept and the legal nature of other measures of criminal-legal nature, their difference from punishment. Since the other measures of criminal-legal character are varied and specific, the author considers that it is difficult to formulate a general definition of such measures. The author distinguishes three approaches in the theory of criminal law on the question about the system of measures under consideration: "wide", "narrow" and "balanced approach." The author adheres to the "balanced approach" and justifies the statement that the organization of other measures of criminal-legal nature can only be based on their legal nature. This leads to the conclusion that conditional sentence, postponement of punishment, postponement of punishment for drug addicts, compulsory measures of educational influence, compulsory measures of medical nature connected with the execution of the sentence should be referred to other measures ofcriminal law. The author substantiates the view that the legislator's decision about systematization of measures considered in Section VI of the RF Criminal Code is inconsistent and illogical. According to the author, the confiscation of property should be provided in the criminal legislation not as other measure of criminal law, but as an additional kind of punishment. Judicial fine should be excluded from the Criminal Code. Because of their specificity and diversity it is hardly expedient to allocate all the other measures of criminal-legal nature in one section of the RF Criminal Code.